MENINGKATKAN KEMAMPUAN MENGENAL BENTUK GEOMETRI MELALUI METODE PROYEK PADA ANAK USIA 5-6 TAHUN DI TK MUTIARA BUNDA KECAMATAN BANGKINANG KOTA - Narulita Narulita; Zulkifli Zulkifli; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The study aims to know the increased ability to know the form of geometry to the group B through the method of the project in Kindergarten Mutiara Bunda District Bangkinang Regency of Kampar. The research is the kind of research a class action or (PTK) which was held in two cycles. Every cycle consists of the planning stage, action, observation, and reflection. The subject of this study is the group B of 15 children in TK Mutiara Bunda. The research be obtained through the method of observation and analysis data that was done by using analysis of the sort of descriptive set of quantitative and qualitative. Research show that this method of project can improve the ability of a familiar geometry to the group B. It can be seen from increasing the percentage of the ability to know the geometry of the child to cycle 1 of 37,10% with the criteria bud (MB) and increased by 35,36% on the second to 50,22% with the criteria developed in accordance with the hope (BSH). So, the method of project can improve the ability to know the alphabet geometry in children age 5-6 years ol in kindergarten Permata Bunda district Bangkinang CityKeyword : The Ability To Know The From Of Geometry, Method of Project